Anthony Bryer with David Winfield, Selina Balance and Jane Isaac, The Post-Byzantine Monuments of the Pontos . A Source -Book - Κιτρομηλίδης, Πασχάλης Μ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2009)
[Δε διατίθεται περίληψη / no abstract available]